Microstructure and mechanical properties of TOP-TIG-wire and arc additive manufactured super duplex stainless steel (ER2594) - Zhang, Xiaoyong; Wang, Kehong; Zhou, Qi; Ding, Jialuo; Ganguly, Supriyo; Marzio, Grasso; Yang, Dongqing; Xu, Xiangfang; Dirisu, Philip; Williams, Stewart W. (Elsevier, 2019)
As the excellent combination of mechanical properties and corrosion resistance for super duplex stainless steel, a prospective method – Wire and Arc Additive Manufacturing – for fabricating this material was proposed, and a wall component was deposited in this study. The microstructure of the as-deposited wall was carefully analyzed along with the variation of mechanical properties. The results revealed that, in the wall-body, the austenite/ferrite phase balance was broken by the overgrowing the austenite phase. During this process, the intergranular secondary austenite leading the increase of austenite phase together with some contributions made by the precipitation of intragranular secondary austenite. Propagation of the intermetallic phases, chi and sigma phase, was not the major reason for the low impact toughness in the last layer area and the root region. Instead, the presence of CrN and “inclusions” (Cr2N and impurities) took the main responsibility not only in the impact toughness but also the ductility. The anisotropic analysis revealed that the UTS and elongation appeared distinct difference in vertical and horizontal direction samples. The varieties in YS were eliminated by the nitrogen work hardening effect to a large extent.
Keywords: TOP-TIG; Wire and arc additive manufacturing; Super duplex stainless steels; CrN Cr2N; Anistropy; Nitrogen work hardening